Optimization of Indole-butyric Acid Competency on Root Elongation of Arecaceae through Micro-propagation: Indole-butyric Acid Competency on Root Elongation of Arecaceae - Khaskheli, Asad Ali; Khaskheli, Muhammad Ibrahim; Rind, Muhammad Rafique; Khaskheli, Asad Ali; Zhang, Li; Panhwar, Khadim Ali (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2020)
In the present study optimization of Indole-butyric Acid (IBA) competency on the root elongation was evaluated. The regenerated shoots were separated and shifted to a new media (MS-Basal) containing various concentrations of (IBA) 0.0, 0.5, 1.0, 2.0, 3.0, and 4.0 mg/L and the observations based on the survival rate (%),initiation of roots at a different interval, encountering the total number of roots per shoot and roots length (cm) was noticed. The plants regenerated on (control) MS basal medium where zero concentration of IBA was used, revealed a relatively (P < 0.05) lower rate of survival (72.50%) as well as no roots observed till the end of the experiment. While MS-Basal medium supplemented with IBA (2.0mg/L) took minimum time to initiate the roots (16.80 days). The highest number of roots (4.48) appeared in the media containing 3mg/L IBA concentration, whilst 0.5 and 4.0mg/L IBA demonstrated significantly (P > 0.05) similar response i.e. 1.83 and 1.70 number of roots respectively, that consequently revealed relatively less number of roots as compared to other concentrations of the media. The MS-Basal media supplemented with 2.0 and 4.0mg/L IBA showed relatively (P < 0.05) longer length of roots (2.45 and 2.22 cm) compared to that of MS-Basal media supplemented with 0.5 and 1.0mg/L IBA (1.46 and 1.60 cm, respectively).Besides these things, MS-Basal media supplemented with 3.0 mg/L IBA showed a higher length of roots than the other media.